Experiences of Family Caregivers in Palliative Care North Kerala: A Qualitative Study - Krishna Raj JS; Surekha A; Kanniyan Binub; Rock Britto; Suguna A (National Journal of Community Medicine, 2026)
Background: Managing caregiving complexities for palliative care patients poses significant challenges, especially within the community-based “Kerala Model” in Calicut, North Kerala, India. This qualitative study explores the lived experiences, unmet needs, coping strategies, and quality of life of family caregivers in this context. Methods: A qualitative descriptive study was conducted using purposive sampling. Three focus group discussions (FGDs) involving 24 primary family caregivers were conducted at two palliative care centres. Data were transcribed verbatim and thematically analysed using Braun and Clarke’s six-phase framework. Trustworthiness was enhanced through peer debriefing, reflexive journaling, and member checking. Results: Among 24 caregivers, 15 (62.5%) were female and 9 (37.5%) males. Spouses (10, 41.7%) and children (9, 37.5%) constituted the majority of caregivers. Six interconnected themes emerged: caregiving competencies, caregiver well-being, social and relational factors, support systems, end-of-life care, and criticism. Caregivers reported inadequate training, emotional and physical exhaustion, social isolation, financial strain, limited practical and psychological support, end-of-life decision-making challenges, and distress related to criticism. Most had provided care for 1-2 years (8, 33.3%), while 7 (29.2%) had provided care for 6 months-1 year. Conclusion: Family caregivers experience multidimensional burdens within Kerala’s community-based palliative care model. Contextually appropriate caregiver training, psychological support, financial assistance, and respite services are needed to strengthen caregiver well-being and coping.